2018
DOI: 10.1186/s12912-018-0318-7
|View full text |Cite
|
Sign up to set email alerts
|

Improving the implementation of patient safety by nursing students using nursing instructors trained in the use of quality circles

Abstract: BackgroundIt is recognised worldwide that the skills of nursing students concerning patient safety is still not optimal. The role of clinical instructors is to instil in students the importance of patient safety. Therefore, it is important to have competent clinical instructors. Their experience can be enhanced through the application of quality circles. This study identifies the effect of quality circles on improving the safety of patients of nursing students. Patient safety is inseparable from the quality of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
(29 reference statements)
0
10
0
Order By: Relevance
“…According to Alquwez (2019), the higher a student's year level or rank, the more skilled and knowledgeable they regarded patient safety. Findings indicate that the higher their study levels, the more chances that they will learn about patient safety values, which leads to a higher level of confidence in patient safety practices (Noviyanti, Handiyani, & Gayatri, 2018).…”
Section: The Attitude Regarding Patient Safetymentioning
confidence: 98%
See 2 more Smart Citations
“…According to Alquwez (2019), the higher a student's year level or rank, the more skilled and knowledgeable they regarded patient safety. Findings indicate that the higher their study levels, the more chances that they will learn about patient safety values, which leads to a higher level of confidence in patient safety practices (Noviyanti, Handiyani, & Gayatri, 2018).…”
Section: The Attitude Regarding Patient Safetymentioning
confidence: 98%
“…According to Alquwez et al ( 2019), the higher the year level of students or the more senior in rank, the more professional and informed about patient safety. Finding shows that the higher the level of their study, the more significant the exposure to learning opportunities relevant to patient safety principles, which leads to a higher level of trust in patient safety practices (Noviyanti, Handiyani, & Gayatri, 2018).…”
Section: The Relationship Between the Demographic Data And The Knowledge Level On Patient Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…This result is in line with an earlier study that reported that nursing students felt confident about their clinical safety skills (Huang et al 2020 :1). However, other studies reported contradictory results showing that nursing students had a low competence on patient safety (Noviyanti, Handiyani & Gayatri 2018 :12). The differences in the results suggest that students tend to overestimate their competence in self-reported measurements only for objective measurements to show that their competence is not that high.…”
Section: Discussion Of the Resultsmentioning
confidence: 98%
“…Patient safety is inseparable from the quality of nursing education. Existing research shows that the introduction of patient safety should be part of the education at all levels of the healthcare system (Noviyanti, 2018). One study stated that the quality of education delivered to nursing students can significantly reduce medical errors and improve the safety culture and quality of service.…”
Section: Introductionmentioning
confidence: 99%